2011
DOI: 10.1063/1.3626468
|View full text |Cite
|
Sign up to set email alerts
|

Charge trapping and detrapping in polymeric materials: Trapping parameters

Abstract: Space charge formation in polymeric materials can cause some serious concern for design engineers as the electric field may severely be distorted, leading to part of the material being overstressed. This may result in material degradation and possibly premature failure at the worst. It is therefore important to understand charge generation, trapping, and detrapping processes in the material. Trap depths and density of trapping states in materials are important as they are potentially related to microstructure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
115
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 153 publications
(121 citation statements)
references
References 17 publications
5
115
0
1
Order By: Relevance
“…Factually, these traps might exist with a range of levels in wide band-gap of insulation material. Typically, it was suggested that shallow and deep traps can be correlated with physical and chemical defects in the polymeric material respectively 7,14,19,24 . Physical defects can be created by changes in crystallinity, morphological structure and molecular weight while chemical defects can be produced by oxidation and hydrolysis process 9,24 .…”
Section: B Model Based On Dual-level Trapsmentioning
confidence: 99%
See 3 more Smart Citations
“…Factually, these traps might exist with a range of levels in wide band-gap of insulation material. Typically, it was suggested that shallow and deep traps can be correlated with physical and chemical defects in the polymeric material respectively 7,14,19,24 . Physical defects can be created by changes in crystallinity, morphological structure and molecular weight while chemical defects can be produced by oxidation and hydrolysis process 9,24 .…”
Section: B Model Based On Dual-level Trapsmentioning
confidence: 99%
“…(iv) Both studies tried to separate traps with a range of energy levels into two equivalent levels 13 or ranges 15 . And it is noteworthy in works based on Chen's model 13,14,19 , the two energy levels, i.e. shallow and deep traps, have been reported relating with physical and chemical defects in polymeric materials respectively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 There are two kinds of charge transport mechanisms, which can represent the charge conduction processes for the shallow trap and the deep trap, respectively. For the shallow traps, the trapped charges can overcome the potential barrier and hop to the neighbour trip site by the effect of thermal vibration, which depends on the temperature and electric field.…”
mentioning
confidence: 99%